FORMULATION OF Sweet Orange Fruit Peel (Citrus x sinensis (L.) Osbeck) ECO ENZIM GEL AND ACTIVITY TEST OF Propionibacterium acnes BACTERIES - Gusrianti, Leli; Yenti, Revi; Arel, Afdhil (Department of Pharmacy, Muhammmadiyah University of Sumatera Barat, 2024)
This study aims to determine the anti-acne activity of a gel preparation from the eco enzyme of sweet orange peel against Propionibacterium acne. The method used in making eco enzymes is fermentation, while for testing antibacterial activity the paper disc diffusion method is used. Sweet orange peel eco enzyme gel formula with concentrations of (F0)0%, (F1)5%, and (F2)10% using carbopol 940. Anti-acne gel preparations were subjected to organoleptic test, pH, homogeneity, viscosity, irritation, stability and antibacterial activity tests against Propionibacterium acne. The research results showed that F0, F1 and F2 met the standard requirements with physical characteristics of a typical sweet orange scent for F1 and F2, as well as a carbopol scent for F0, a transparent white color for F0 and a pale yellow and yellow color for F1 and F2. It is thick and slightly viscous with a pH of 5, has a homogeneous shape, a viscosity of 3000-50000 cPs, is stable against cold and hot temperatures, and does not irritate the skin. The antibacterial activity test showed that all gel formulations could not inhibit the growth of Propionibacterium acne bacteria.